Calibration of a TDR equipment to moisture measurement in soils - Tommaselli, José Tadeu Garcia; Bacchi, Osny Oliveira Santos (Pesquisa Agropecuaria Brasileira, 2001)
The aim of this study was to obtain the calibration curves for a TDR (Time Domain Reflectometry) equipment using five soils from the Piracicaba, SP, Brazil. The suitability of the built-in and generic calibration curves was also tested. Individual fitted curves for each soil showed determination coefficients (R2) of about 0.99 and the fitted curve for all five soils together showed a value of R2 = 0.976. The standard error of estimate analysis has pointed out that generic curves are not suitable for more sensible applications, such as for absolute determination of soil water content. Comparison tests among fitted curves, generic curve and the equipment curve, pointed out that the first one is superior to the others. This study showed also that the equipment built-in calibration curve is not suitable for soil water content determinations for the five studied soils.